Exploring joint patterns of brain structure and function in inflammatory bowel diseases using multimodal data fusion - Thomann, Anne K.; Schmitgen, Mike; Kmuche, Dagny; Ebert, Matthias; Thomann, Philipp; Szabo, Kristina; Gass, Achim; Griebe, Martin; Reindl, Wolfgang; Wolf, Robert Christian (Neurogastroenterology and motility, 2021)
Background A growing number of neuroimaging studies suggest distinct neural changes in inflammatory bowel diseases (IBDs). Whether such changes may show similar spatial patterns across distinct neural features within and between specific IBD is unclear. To address this question, we used multivariate multimodal data fusion analysis to investigate structure/function modulation in remitted patients with Crohn's disease (CD) and ulcerative colitis (UC). Methods Patients with IBD (n = 46; n = 31 with CD, n = 15 with UC) in stable remission and 17 healthy controls (HC) underwent structural magnetic resonance imaging (sMRI) and resting-state functional magnetic resonance imaging (rs-fMRI) as well as cognitive testing. Anxiety, depression, and fatigue were assessed using self-rating questionnaires. sMRI data were analyzed via voxel-based morphometry (VBM) and rs-fMRI data via amplitude of low-frequency fluctuations (ALFFs) and regional homogeneity (ReHo). Detection of cross-information between VBM, ALFF, and ReHo was conducted by means of a joint independent component analysis (jICA), followed by group-inference statistics. Key results Joint independent component analysis detected structural alterations in middle frontal and temporal regions (VBM), and functional changes in the superior frontal gyrus (ReHo) and the medial as well as inferior frontal, inferior temporal, rectal, and subcallosal gyrus (ALFF). One joint component of extracted features of the three modalities differed significantly between IBD patients and controls (p = 0.03), and most distinctly between HC and patients with UC. Conclusions and inferences Using a multivariate data fusion technique, this study provides further evidence to brain alterations in IBD. The data suggest distinct neural differences between CD and UC, particularly in frontotemporal regions.
First published: 28 December 2020
Gesehen am 12.01.2022